Budidaya Ikan Gurami Osphronemus gourami: Teknis Pembenihan dan Analisa Kelayakan Usaha - Andri Iskandar; R Tresia Pinem; Giri Maruto Darmawangsa; Andri Hendriana; Wahyu Puji Astiyani; Muslim Muslim (Universitas Batangahari Jambi, 2022)
Giant gouramies Oshpronemus gouramy is a fishery commodity and a group of freshwater perciform fishes. This culture technical study was carried out at Freshwater Aquaculture Departement Sendangsari, Yogyakarta which aims to increase knowledge and skills in the cultivation of freshwater pomfret directly, in terms of both hatchery and growth up. Hatchery activities in Freshwater Aquaculture Departement Sendangsari using the ratio of male and female spawning 1:3 naturally. Hatchery activities produce fecundity rate (FR) 81.08%, hatching rate (HR) 90.02%, survival rate (SR) of larvae 71.74%, and SR of seeds 82%. Gouramy seeds was sold to farmers size 4 until 6 cm/individual in Sendangsari, Yogyakarta